Reformulation of Additional Criminal Sanctions in Law No. 2 of 2025 on Mineral and Coal Mining Based on Green Mining Principles - Haryadi, Dwi; Zulkarnain, Iskandar; Sari, Rafiqa (Society, 2025)
One of the principles contained in Law No. 2 of 2025, as the Fourth Amendment to Law No. 4 of 2009 on Mineral and Coal Mining, is sustainability and environmental responsibility as manifestations of green mining. In licensed mining activities, there is an obligation to carry out post-mining management and land reclamation as environmental restoration measures. However, in illegal mining, which clearly causes environmental damage, there is no clarity regarding who bears responsibility. The current criminal sanctions are limited to imprisonment and fines. Imprisonment has no impact on environmental restoration, while fines imposed in court decisions are generally insufficient to cover the costs of environmental recovery. Although additional criminal sanctions exist, they do not explicitly regulate such obligations. This is where the urgency of this study lies: ensuring that there is a legally responsible party for environmental restoration. The purpose of this research is to analyze existing regulations on additional criminal sanctions and to formulate a green-mining-oriented reform. This study employs a normative juridical approach through statutory analysis and case studies based on court decisions, using secondary data comprising primary, secondary, and tertiary legal materials. The findings reveal, first, that the current formulation of criminal acts and additional criminal sanctions has not yet been oriented toward environmental restoration responsibility. Second, it is essential to reformulate the additional criminal sanctions to incorporate obligations for environmental recovery arising from criminal acts. The legal implications are twofold: theoretically, this strengthens the recognition of the environment as a victim that must be protected; practically, it ensures legal certainty for environmental restoration through court decisions, thereby affirming the existence and effectiveness of environmental law enforcement.